(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
This paper applies recent advances in analysing systems behaviour based on thermodynamics to investigating the physical basis of biology and so provide a physical definition of life. The definition of life provided also provides a physical basis for Dawkins’s selfish gene theory. The systems analysis of prokaryote evolution and development herein also describes an example of Dawkins’s extended phenotype emerging during prokaryote evolution. This paper also identifies the biophysical basis for the emergence of ecological ‘r’ and ‘K’ reproductive strategies in prokaryotes. Finally, part of this analytical approach is applied to recent work on the origin of life and used to describe its alignment with a particular hypothesis for the origin of life on Earth.